2019
DOI: 10.1002/ffj.3546
|View full text |Cite
|
Sign up to set email alerts
|

Pore size matching up: A novel insight into cotton textile aromatic finishing

Abstract: Aromatic reservation is one of the key evaluation index of textiles which be finished with fragrant micro‐/nanocapsules, and some researches discover that when the fragrant micro‐/nanocapsules penetrating into the spacing of textiles, the resulting aromatic textiles own much better carrying capability of micro‐/nanocapsules. Based on these phenomena, hence in our research, the matching up between pore sizes of cotton textile and sizes of fragrant micro‐/nanocapsules is investigated systematically in order to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Liu et al studied the matching between textile cotton pore sizes and micro/nanocapsule sizes. 149 The nanocapsules for finishing cotton fabric had the better durability of washing than microcapsules because they penetrated more into the cotton fiber. Still related to the size of the microcapsule, are crosslinkers, which can be molecules of different sizes, as an example, there is a tannic acid larger than CA.…”
Section: Comparison Of Encapsulation Methodsmentioning
confidence: 99%
“…Liu et al studied the matching between textile cotton pore sizes and micro/nanocapsule sizes. 149 The nanocapsules for finishing cotton fabric had the better durability of washing than microcapsules because they penetrated more into the cotton fiber. Still related to the size of the microcapsule, are crosslinkers, which can be molecules of different sizes, as an example, there is a tannic acid larger than CA.…”
Section: Comparison Of Encapsulation Methodsmentioning
confidence: 99%
“…Plant extract-loaded NP-mediated functionalization has also been widely applied to textile fabrics, with the main goal of obtaining prolonged biological effects [ 186 ]. One example explored citronella oil encapsulated within CS-based emulsions (having 79–93 nm in size on the course of 14 days of storage) further stabilized with citric acid onto a cotton knit (100% cotton textile, pore surface area of 20–90 µm 2 , distances within interyarn: 10–70 µm, distances within interfiber (intrayarn): 2–6 µm, and distances within pore (interfiber): 10–90 nm).…”
Section: Biomedical Applications: Fiber-based Systemsmentioning
confidence: 99%
“…Indeed, the aromatic retention of cotton textiles finished by nanocapsules was much greater than the same textiles finished with microcapsules (28.84% vs. 1.55%) after 10 cycles of washing. The authors demonstrated that nanocapsules can penetrate better into the pores of the cotton textiles [ 114 ]. To overcome the issue related to the poor combination fastness and duration in the textiles, several approaches were employed in the past, using chemical binders or crosslinking agents.…”
Section: Applications Of Micro-/nanoencapsulated Fragrances and Flmentioning
confidence: 99%